2019
DOI: 10.1126/scisignal.aat7527
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic blockade of activin-A improves NK cell function and antitumor immunity

Abstract: Natural killer (NK) cells are innate lymphocytes that play a major role in immunosurveillance against tumor initiation and metastatic spread. The signals and checkpoints that regulate NK cell fitness and function in the tumor microenvironment are not well defined. Transforming growth factor–β (TGF-β) is a suppressor of NK cells that inhibits interleukin-15 (IL-15)–dependent signaling events and increases the abundance of receptors that promote tissue residency. Here, we showed that NK cells express the type I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 79 publications
4
60
0
Order By: Relevance
“…Inhba is a ligand in the transforming growth factor β (TGF-β) superfamily, which has been shown to regulate Ido1 via the Smad signaling pathway (22). A recent study has demonstrated that inhba plays a crucial role in inhibiting NK cell proliferation and production of granzyme B thereby leading to impairment of tumor susceptibility to NK cell-mediated killing (23). Finally, the Dtx4 E3-Ubiquitin ligaseknown to promote TBK1 degradation and Type 1 interferon response (24)-was found to be upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…Inhba is a ligand in the transforming growth factor β (TGF-β) superfamily, which has been shown to regulate Ido1 via the Smad signaling pathway (22). A recent study has demonstrated that inhba plays a crucial role in inhibiting NK cell proliferation and production of granzyme B thereby leading to impairment of tumor susceptibility to NK cell-mediated killing (23). Finally, the Dtx4 E3-Ubiquitin ligaseknown to promote TBK1 degradation and Type 1 interferon response (24)-was found to be upregulated.…”
Section: Discussionmentioning
confidence: 99%
“…As technology has advanced, larger numbers of proteins have been identified in an unbiased manner, demonstrating the growing utility of proteomics (276,277). A more recent study used proteomic analysis to identify proteins important for NK cell proliferation and pointed a pathway toward increasing the activity of NK cells in a tumor model through therapeutic blockade (278).…”
Section: Omics Studies On Nk Cell Activationmentioning
confidence: 99%
“…Although ILC1 are tissue resident and unlikely to migrate to other tissues (7)(8)(9), their function in cancer is poorly understood. Recent studies have revealed that transforming growth factor-beta (TGF-β) signaling (either by TGF-β itself or indirectly by Activin-A) can suppress cellular metabolism and effector functions (10)(11)(12). This suppressive signaling drives the upregulation of ILC1-related markers in circulating mouse or human NK cells, suggesting the possibility of intercellular plasticity which could be important within the tumor microenvironment (TME) (11,13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have revealed that transforming growth factor-beta (TGF-β) signaling (either by TGF-β itself or indirectly by Activin-A) can suppress cellular metabolism and effector functions (10)(11)(12). This suppressive signaling drives the upregulation of ILC1-related markers in circulating mouse or human NK cells, suggesting the possibility of intercellular plasticity which could be important within the tumor microenvironment (TME) (11,13,14). NK cell cytotoxicity can be controlled by many stimulatory (NKp30, NKp44, NKp46, CD16) and inhibitory (PD1, TIM3, TIGIT, KLRG1) surface receptors (15).…”
Section: Introductionmentioning
confidence: 99%